1995
DOI: 10.1007/bf00191365
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial abnormalities of muscle tissue in mice with juvenile visceral steatosis associated with systemic carnitine deficiency

Abstract: A mouse with juvenile visceral steatosis (the JVS mouse) has been recognized as a novel animal model for systemic carnitine deficiency. We examined cardiac, skeletal and smooth muscle cells in JVS and control mice by light and electron microscopy. Cardiac and skeletal muscle cells of these mice at 4 weeks of age exhibited a ragged-red appearance after trichrome staining. Electron microscopy, demonstrated increased numbers of mitochondria and lipid droplets in the cells. Compression or distortion of the myofibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Role of carnitine in brown adipocytes K Ozaki et al and display a severe carnitine deficiency and the accumulation of lipid droplets in various cells (hepatocytes, renal tubular epithelial cells, cardiac myocytes, and striated myocytes). [12][13][14]17 L-carnitine administration increases the carnitine concentration and eliminates the accumulation of lipids in the liver, heart, and skeletal muscle of JVS mice. 12,14,17,26 However, tissue carnitine levels in the heart, liver, and skeletal muscle are significantly lower than those in controls, even after L-carnitine administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Role of carnitine in brown adipocytes K Ozaki et al and display a severe carnitine deficiency and the accumulation of lipid droplets in various cells (hepatocytes, renal tubular epithelial cells, cardiac myocytes, and striated myocytes). [12][13][14]17 L-carnitine administration increases the carnitine concentration and eliminates the accumulation of lipids in the liver, heart, and skeletal muscle of JVS mice. 12,14,17,26 However, tissue carnitine levels in the heart, liver, and skeletal muscle are significantly lower than those in controls, even after L-carnitine administration.…”
Section: Discussionmentioning
confidence: 99%
“…11 The JVS phenotype is inherited in an autosomal recessive manner and is characterized by growth retardation, fatty liver, hypoglycemia, hyperammonemia, and cardiac hypertrophy. [12][13][14][15][16][17][18][19] Carnitine administration improves the characteristic symptoms of JVS mice. 15,17,18,20 Moribund JVS mice display continuous shivering, which is attributable to a decrease in heat production and an enhanced sensitivity to cold.…”
mentioning
confidence: 99%
“…Thus, these results strongly suggest the presence of some novel heart-specific transcription/replication factors controlling the mitochondrial number, because the increase in mitochondrial number in JVS mice was observed only in the cardiac and skeletal muscle cells. 6,7) In addition, Bergeron et al reported that chronic activation of AMP-activated protein kinase (AMPK), which is caused by energetic stress by treatment with the creatine analog b-guanidinopropionic acid (b-GPA), might result in mitochondrial biogenesis in skeletal muscle. 46) They suggested that activation of AMPK also activated NRF-1, which thereby resulted in an increase in the cytochrome c content.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In JVS mice, the reabsorption system of carnitine in the kidney is defective; 5) and, as a result, carnitine levels are low in the plasma, liver, skeletal muscle, and heart. 4,6,7) Recently, it was proved that primary systemic carnitine deficiency in JVS mice is caused by a missense mutation in a gene encoding the sodium ion-dependent carnitine transporter. 8,9) Horiuchi et al reported that carnitine administration corrected growth retardation and abnormal gene expression of urea-cycle enzymes and was partly effective in ameliorating the fatty liver and in suppressing the cardiac hypertrophy.…”
mentioning
confidence: 99%
See 1 more Smart Citation